Markers of kidney tubule dysfunction and injury and long-term risk of acute kidney injury following coronary artery bypass graft surgery - Lauren Shingler; Ashutosh Tamhane; Ching-Min Chu; Jennifer A. Frey; Emily B. Levitan; Suzanne E. Judd; Alexander L. Bullen; Edward D. Siew; Joseph V. Bonventre; Michael G. Shlipak; Byron Jaeger; Jesse C. Seegmiller; et al. (PLoS ONE, 2026)
Background Approximately one in five patients undergoing coronary artery bypass graft (CABG) surgery will develop post-operative acute kidney injury (AKI). We sought to determine whether biomarkers of kidney tubule dysfunction and injury are associated with long-term risk of acute kidney injury (AKI) after coronary artery bypass graft (CABG) surgery. Methods We performed a cohort study using data from the REasons for Geographic And Racial Differences in Stroke (REGARDS), a national, population-based, longitudinal cohort study of 30,239 U.S. adults aged ≥45 years. Of 760 REGARDS participants who underwent CABG surgery after their REGARDS baseline visit, we excluded those with a history of dialysis or kidney transplant, missing laboratory data or with illegible or erroneous records, leaving 394 in the analysis. Exposures included urinary biomarkers of kidney tubule dysfunction (urine alpha-1 microglobulin [A1M], uromodulin [UMOD] and epidermal growth factor [EGF]) and injury (kidney injury molecule-1 [KIM-1]), measured at an average of 5.5 years before CABG surgery. The primary outcome was AKI development following CABG surgery, defined as an increase in serum creatinine ≥0.3 mg/dL from 48 hours prior to CABG surgery to end of hospitalization. Results Of 394 participants, 176 (45%) experienced post-CABG surgery AKI. Higher baseline urine A1M was associated with higher odds of AKI (adjusted OR 1.34 per 2-fold higher A1M, 95% Confidence Interval (CI): 1.00–1.80). Higher urine UMOD was associated with lower odds of AKI (adjusted OR 0.77 per 2-fold higher UMOD, 95% CI 0.62–0.95). Higher EGF showed a tendency towards lower odds of AKI (adjusted OR 0.79 per 2-fold higher EGF, 95% CI 0.59–1.05). KIM-1 was not associated with AKI (adjusted OR 0.92 per 2-fold higher KIM-1, 95% CI 0.77–1.10). Conclusions Select biomarkers of kidney tubule dysfunction, but not injury, are associated with future risk of AKI after CABG surgery. Biomarkers measured years before surgery may predict post-CABG surgery AKI.